Les taux de commission sur les transactions boursières au Canada : Acte II - Saint-Pierre, Jacques (L'Actualité économique, 1983)
This is the second part of a study about what could be called an economic play or drama: the deregulation of commission rates on stock exchange transactions. This article presents an economic analysis of the long-standing policy in Canada of charging minimum commission on stock transaction. The discussion draws heavily on the arguments put forward by the Montreal Exchange as a part of its recent ongoing defense of fixed commission. The arguments fall into three categories: (1) the economic approach to the analysis of the brokerage business (uncertainty in product quality) (2) the information produce by the brokerage industry are public goods because of externalities and (3) the structure of the brokerage industry. According to the Exchange's logic, the elimination of the practice of price fixing would lead to a less efficient capital market because of the reduction in the production of information and to an increase in the concentration in the brokerage business. The analysis presented in this article leads to the conclusion that the Exchange's case is faulty in terms of both its theory and its empirical proofs and that minimum commission rates on stock exchange transactions cannot be justified on economic grounds.